STRATEGI PEMASARAN PADA PRODUK TABUNGAN HAJI DI BANK SYARIAH INDONESIA KANTOR CABANG PEMBANTU ROGOJAMPI - Habibulloh Habibulloh (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2022)
Marketing strategy is defined as the analysis of development strategies and implementation of activities in the target market determinant strategy for products in business units, setting marketing objectives, and implementation development, as well as the management of market position-determining marketing program strategies designed to meet the desires of target market consumers. This study is a study with a descriptive-cauldronative approach. This research was conducted at Bank Syariah Indonesia Rogojampi Auxiliary Branch Office. The subject in the study was a supervisor, the Consumer Business Relations Manager (CBRM). This research aims to find out how the marketing strategy of hajj savings products in Bank Syariah Indonesia Rogojampi Auxiliary Branch Office. While the method of data collection in this study uses interviews, while the data analysis method used is interviewing, observation, and documentation techniques. The results of qualitative research show that the marketing strategy of Hajj savings products is to utilize the moment at the end of the service such as cross selling, dor to door related to hajj savings products. Such a way is the most effective way to get prospective customers, because it meets face to face and presents hajj savings products like what is in Bank Syariah Indonesia KCP Rogojampi.